Does Ramadan influence the returns and volatility? Evidence from Shariah index in India. Issue 4 (8th July 2019) - Munusamy, Dharani
Abstract : Purpose: Muslim's hope that the holy month of Ramadan will create something more valuable for them. Through fasting and good actions, they can get rewarded twice than they normally can achieve. With this motivation, the purpose of this paper is to investigate the holy month of Ramadan effect on the returns and volatility of the Shariah index in India. Design/methodology/approach: Using the ordinary least square methods, this paper examines the impact of Ramadan effect on the returns of the Shariah index in India. This paper further investigates the impact of the holy month of Ramadan effect on the volatility of the Shariah index by applying GARCH-modified models. This paper categorizes the Ramadan days into three parts, namely God's Mercy, God's Forgiveness and Emancipation from hellfire to examine the relationship between the Ramadan effect and the returns and volatility of the Shariah index in India. Findings: The results show that the returns during the month of Ramadan as a whole are statistically significant. The results further motivate that its last ten days have high influences than other days over the period. Finally, the study examines the Ramadan effect on volatility by applying GARCH modified models and finds an evidence of Ramadan effect during the first ten days of Ramadan month. Originality/value: The positive impact of Ramadan increases on the days associated with higher worship intensity. The study provides an important information to the ethical investors to invest in the Shariah stocks during Ramadan days. This information is very useful for the investors to get an abnormal return during the Ramadan days.